Detection of epitasis, additive and dominance variation in rice (Oryza sativa L.) using triple test cross analysis - N.R. Koli, Chandra Prakash, R.K. Mahawar ,B.L.Kumhar and S.S.Punia (Electronic Journal of Plant Breeding, 2014)
An investigation was carried out to detect the epistasis, additive and dominance components of genetic variance for yield and yield attributing traits through triple test cross analysis, involving three testers (P1, P2 and their F1) and ten lines of rice. The estimate of total epistasis was found non-significant for all the traits while partitioning of total epistasis revealed that, i type of epistasis (additive x additive) were highly significant for yield per plant, plant height, number of panicle per meter square, panicle length and number of grains per panicle. The additive (D) and dominance (H) effects were highly significant for yield per plant, plant height, panicle length, number of grains per panicle and 1000 grain weight. The degree of dominance (H/D)1/2 was less than the unity indicating, partial dominance for plant height, panicles / m2 and 1000 grain weight whereas, yield per plant, panicle length and number of grains per panicle indicating over dominance (>1) . Since, the predominance components of epistasis in autogamous crop is additive x additive (i type), we suggest that the selection may be delayed to later generation for the improvement of yield through yield components in rice.